Golden Functions

Algebra Level 3

Let f ( x ) f(x) be the larger positive real number and g ( x ) g(x) be the smaller positive real number such that f ( x ) g ( x ) = x f(x) \cdot g(x) = x and f ( x ) g ( x ) = x f(x) - g(x) = x .

For example, for x = 1 x = 1 , f ( 1 ) = ϕ = 5 + 1 2 f(1) = \phi = \frac{\sqrt{5} + 1}{2} and g ( 1 ) = 5 1 2 g(1) = \frac{\sqrt{5} - 1}{2} , since 5 + 1 2 5 1 2 = 1 \frac{\sqrt{5} + 1}{2} \cdot \frac{\sqrt{5} - 1}{2} = 1 and 5 + 1 2 5 1 2 = 1 \frac{\sqrt{5} + 1}{2} - \frac{\sqrt{5} - 1}{2} = 1 .

If f ( x ) + g ( x ) = 55 5 f(x) + g(x) = 55\sqrt{5} , find x x .


The answer is 121.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Using the property, ( a + b ) 2 ( a b ) 2 = 4 a b (a + b)^2 - (a - b) ^2 = 4ab

( f ( x ) + g ( x ) ) 2 = ( f ( x ) g ( x ) ) 2 + 4 f ( x ) g ( x ) (f(x) + g(x))^2 = (f(x) - g(x))^2 + 4f(x)g(x)

( 55 5 ) 2 = x 2 + 4 x \Rightarrow (55\sqrt 5)^2 = x^2 + 4x

x = 4 + 16 ( 4 × 15125 ) 2 = 2 + 15129 = 2 + 123 = 121 \Rightarrow x = \dfrac {-4 + \sqrt{16 - (-4\times 15125)}}{2} = -2 + \sqrt {15129} = -2 + 123 = \boxed{121}

Note: I have considered positive sign for the square root term as we are looking for positive value of x . x.

Nice solution!

David Vreken - 2 years, 6 months ago

Log in to reply

Thank you :)

A Former Brilliant Member - 2 years, 6 months ago
Chew-Seong Cheong
Nov 28, 2018

f ( x ) g ( x ) = x Squaring both sides f ( x ) 2 2 f ( x ) g ( x ) + g ( x ) 2 = x 2 Given that f ( x ) g ( x ) = x f ( x ) 2 2 x + g ( x ) 2 = x 2 f ( x ) 2 + g ( x ) 2 = x 2 + 2 x \begin{aligned} f(x) - g(x) & = x & \small \color{#3D99F6} \text{Squaring both sides} \\ f(x)^2 - 2{\color{#3D99F6}f(x) g(x)} + g(x)^2 & = x^2 & \small \color{#3D99F6} \text{Given that }f(x)g(x) = x \\ f(x)^2 - 2{\color{#3D99F6}x} + g(x)^2 & = x^2 \\ \implies f(x)^2 + g(x)^2 & = x^2 + 2x \end{aligned}

Now we have:

f ( x ) + g ( x ) = 55 5 Squaring both sides f ( x ) 2 + 2 f ( x ) g ( x ) + g ( x ) 2 = 15125 Recall f ( x ) 2 + g ( x ) 2 = x 2 + 2 x x 2 + 2 x + 2 x = 15125 x 2 + 4 x 15125 = 0 ( x 121 ) ( x + 125 ) = 0 x = 121 SInce x > 0 \begin{aligned} f(x) + g(x) & = 55\sqrt 5 & \small \color{#3D99F6} \text{Squaring both sides} \\ {\color{#3D99F6}f(x)^2} + 2f(x) g(x) + \color{#3D99F6}g(x)^2 & = 15125 & \small \color{#3D99F6} \text{Recall }f(x)^2+g(x)^2 = x^2 + 2x \\ {\color{#3D99F6}x^2 + 2x} + 2x & = 15125 \\ \implies x^2 + 4x - 15125 & = 0 \\ (x-121)(x+125) & = 0 \\ \implies x & = \boxed{121} & \small \color{#3D99F6} \text{SInce }x > 0 \end{aligned}

Very nice solution!

David Vreken - 2 years, 6 months ago

Log in to reply

Glad that you like it.

Chew-Seong Cheong - 2 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...